Antimicrobial stewardship program for gastrointestinal surgeries at a Vietnamese tertiary hospital - Pham, Hong Tham; Mai-Phan, Tuong-Anh; Nguyen, Anh Dung; Nguyen, Van-Quang-Huy; Tran, Minh-Hoang (Frontiers in Medicine, 2024)
Background Antimicrobial Stewardship Programs (ASP) have been applied widely in high-resource countries to prevent surgical site infections (SSI). Evidence favoring ASP interventions (ASPi) in gastrointestinal surgeries from low and middle-income countries has been limited, especially in antimicrobial prophylaxis. We aimed to investigate this gap at a Vietnamese tertiary hospital. Methods We conducted a retrospective cohort study on patients undergoing clean-contaminated surgeries in 2015 who received standard of care (SoC) or SoC + ASPi. Primary outcome was 30-day SSI incidence. Secondary outcomes included length of stay (LoS) after surgery (days), cost of antibiotics, and cost of treatment (USD). Results were controlled for multiplicity and reported with treatment effect and 95% confidence interval (95%CI). A predictive model was built and cross-validated to detect patients at high risk of SSI. Results We included 395 patients for analysis (48.1% being female, mean age 49.4 years). Compared to patients receiving SoC, those with SoC + ASPi had a lower incidence of 30-day SSI (−8.8, 95%CI: −16.0 to −1.6, p = 0.042), shorter LoS after surgery (−1.1 days, 95%CI: −1.8 to −0.4, p = 0.004), and lower cost of antibiotics (−37.3 USD, 95%CI: −59.8 to −14.8, p = 0.012) and treatment (−191.1 USD, 95%CI: −348.4 to −33.8, p = 0.042). We estimated that by detecting patients at high risk of SSI with the predictive model and providing prophylactic measures, we could save 398120.7 USD per 1,000 cases of SSI. Conclusion We found that ASPi were associated with a reduction in risks of SSI, hospital stays, and cost of antibiotics/treatment in a Vietnamese tertiary hospital.